Pengetahuan Guru PAUD Tentang KPSP (Kuesioner Pra Skrining Perkembangan) sebagai Alat Deteksi Tumbuh Kembang Anak - Dewi Eko Wati (Faculty of Teacher Training and Education, Universitas Muhammadiyah Surakarta, 2016)
Children are a very important part in the survival of a nation. Kids are human resources for the development of a nation, a determinant of the future, and the successor generations of the family and the nation. Therefore, they must be in a healthy condition. Efforts to create a healthy generation should be considered, especially in the golden age (the golden period) that occurs at the age of 0-6 years. Therefore, it is necessary to process the detection and stimulation of growth and development for the creation of the next generation of quality that can grow and develop physically, emotionally, and socially. This study aimed at describing knowledge about early childhood teachers KPSP as a tool for early detection of child development. Subjects in this study amounted to 38 people who already have experiences in teaching in early childhood. The research method used is quantitative research. The research instrument used questionnaires and interviews. Data were analyzed using qualitative descriptive analysis. The results of research on teacher's knowledge of the KPSP showed that 73.7% of the subjects had heard of KPSP but only 2.6%, or 1 out of 38 men who were able to conclude and give advice on the test results KPSP are certainly capable of performing appropriate testing standards. It shows the teacher's knowledge of the KPSP is low. All respondents stated KPSP needs to be given to children in kindergarten as a tool of detection of child development. In general it can be concluded that the positive attitude of the teachers accept their KPSP for kindergarten children. The obstacle faced by teachers in conducting detection using KPSP is the lack of socialization or information and training on KPSP.